A cross-sectional study of demographic and clinical profile of HIV patients at ART center of tertiary care hospital - Anil Kumar Agarwal; Arun Kushwah; Pradeep Verma; Ramniwas Mahore; Rani Verma (Asian Journal of Medical Sciences, 2022)
Background: India has the third largest number of people living with HIV/Acquired immunodeficiency syndrome (AIDS). It is important to understand the presentation of HIV disease in the local context and culture. Aims and Objectives: The present study is aimed at identifying the socio-demographic characteristics, clinical presentations of HIV/ AIDS patients, opportunistic infections (OI), and the possible risk factors for acquiring HIV infection. Materials and Methods: A descriptive cross-sectional study was conducted on HIV patients from September 2021 to December 2021. The HIV-positive patients of all age groups and all categories were included in the study. However, the clinical staging was done according to the World Health Organization (WHO) classification of HIV/AIDS. Data were expressed as mean and percentage proportion with chi square test for measuring statistically significance. Results: Among 140 HIV patients 88 (62.9%) were males. More than half were 101 (72.1%) in the reproductive age group 18–40 years with mean age 35±11.5 years. The commonest mode of HIV transmission was heterosexual 114 (81.4%). Maximum belonged to social Class IV 51 (36.4%) and Class III 47 (33.6%) of socioeconomic status. Fever 92 (65.7%), weight loss 82 (58.7%), and cough 68 (48.6%) were the common presenting. Pulmonary tuberculosis and diarrhea were the most predominant secondary OI accounting for 46 (32.9%) and 35 (25.0%), respectively. More than half 82 (58.6%) of patients were in the WHO clinical Stage II of HIV disease. CD4 counts of the patients were significantly inversely correlated with the number of symptoms and the number of OI. Conclusion: There was a high frequency of behavioral risk factors, together with unawareness among HIV patients, socio- demographic, and clinical profile of study participants reflects an impact of early case detection and timely institution of highly active antiretroviral therapy.